PERANAN SISTEM INFORMASI MANAJEMEN DALAM RANGKA PENINGKATAN DUNIA PARIWISATA INDONESIA - Sumaryanto - - (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2009)
Abstract Our Challenge more and more felt by since early the happening of monetary crisis before year-end 1997, even up to now even also still felt by its impact. Riot for the shake of despicable riot is which knock over all angle of fatherland of is condition of this, so that a number of area owning many potency of “wisata” and tourism activity experience of the drastic degradation in number domestic and also foreign tourist visit. The collapse is national economics in this time, especially as overseas debt. Effect, hence effort the effort economics base on the domestic strength start to become the expectation. One of them is object tourism which is spread over in all Indonesia. Nowadays mankind of mankind of Indonesia tourism have to can look for the correct strategy to overcome the economic business resistance and also cultural and political resistance from outside to go forward to become one of the opportunity and alternative, at least with a purpose to prevent the Indonesia tourism become to retreat rear. Keywords: Tourism World, Information System Management, E- Government.